Kepemimpinan Partisipatif Kepala Sekolah dalam Meningkatkan Citra Lembaga Pendidikan SD Muhammadiyah Tegalgede Karanganyar dan MI Muhammadiyah Mergomulyo Matesih Tahun 2023-2024 - Syahrul Shidiq, M; Sabar Narimo; Bambang Sumardjoko (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
This article aims to describe the participative leadership model of school principals at SD Muhammadiyah Tegalgede and MI Muhammadiyah Mergomulyo and identify its influence on improving the image of the institution. Using a qualitative approach with interview, observation and documentation methods, this research found that participatory leadership in both institutions was successful in improving the image of educational institutions. Principals at both institutions lead withintegrity and dedication, which fosters effective collaboration. These findings show that participative leadership principles can be adapted to suit the characteristics of each institution, improving the quality of education and the image of the institution as a whole.